Non‐physician providers as clinical providers in cystic fibrosis: Survey of US programs123. Issue 4 (19th June 2012) - Brown, Rebekah F.; Willey‐Courand, Donna Beth; George, Cindy; McMullen, Ann; Dunitz, Jordan; Slovis, Bonnie; Perkett, Elizabeth
Abstract Background and Methods Non‐physician providers (NPPs) including nurse practitioners (NPs) and physician assistants (PAs) are important members of CF care teams, but limited data exist about the extent NPPs are involved in CF care. A subcommittee was established by the CF Foundation to gather information about current involvement of NPPs. Surveys were sent to adult, pediatric and affiliate CF program directors (PDs) and NPPs working in US CF programs. Results Responses were received from 108 PDs (49% pediatric, 34% adult, 17% affiliate). Overall, 53% of the 108 programs had NPPs and 70% had or planned to hire NPPs. Reasons for NPP use included ideal clinical role (75%), expansion of services (72%), and physician shortage (40%). The survey collected 73 responses from NPPs (96% NPs, 4% PAs) who worked in pediatric (49%), adult (29%), affiliate (3%), or multiple programs (19%). Training occurred on the job in 88% and from prior CF experience in 21%. NPPs provided coverage in outpatient clinics (82%), inpatient care (64%), and weekend and/or night call (22%). In addition to clinical roles, NPPs are involved in education (95%), research (81%), and leadership (55%). The major obstacle reported by PDs and NPPs was billing with only 12% of programs reporting NPP salaries covered by billing revenue alone. Salary support included hospital support (67%), billing (39%), center grant (35%), and other grant/contract (25%). NPPs bill for outpatient and inpatient care in 65% and 28% of programs, respectively. Conclusions NPPs are working with physicians in many centers and have the potential to help meet the increasing clinical workforce demands. Further evaluation of financial issues is indicated to continue the support of NPP jobs in CF. Roles and expectations need to be clearly defined. Initial and ongoing training standards and opportunities should be explored. Pediatr Pulmonol. 2013; 48:398–404. © 2012 Wiley Periodicals, Inc.